Nonreductive Physicalism and Mental Causation - Amen, Miguel (Journal of Business and Legal Sciences / Revista de Ciências Empresariais e Jurídicas, 2006)
I want now to consider what the correct way to understand overdetermination could tell us about the exclusion problem. But what is a better understanding of overdetermination? I think the following example, to be understood as a counterexample to Bennett's test, can lead the way.